Effect of Al2O3nanoparticles on grain sizes and dielectric properties of BaFe1/2Nb1/2O3ceramics - C. Warangkanagool (2018)
In this research, the effect of Al 2 O 3 nanoparticles on grain size and dielectric properties of BaFe 1/2 Nb 1/2 O 3 (BFN) ceramics were investigated. The powder was prepared by the conventional mixed oxide method and calcined at 900-1200°C for 4h. The optimum temperature for calcinations the pure phase, was found to be about 1100°C. The calcined powders and Al 2 O 3 nanoparticles (0.5, 1 and 2 vol%) were ball milled with 1 wt% PVA in ethyl alcohol for 12 h using the same method as mentioned earlier. The slurry was dried, sieved and pressed into a disc shape and sintered at 1350°C for 4h with heating rate of 5°C/min. The microstructure was examined by scanning electron microscope (SEM). The dielectric constant and dielectric loss of BFN ceramics with 0, 0.5, 1 and 2 vol% Al 2 O 3 nanoparticles were measured at 1 kHz frequency at room temperature using LCR meter. The results show that, the average grain sizes of BFN ceramics were found to decrease with the addition of the Al 2 O 3 nanoparticles. The dielectric loss of BFN ceramics with Al 2 O 3 nanoparticles was decreased about 40-50% of pure BFN ceramics. Copyright © Taylor & Francis Group, LLC.